Farmers' challenges in adopting soil health card recommendations in Saharsa, Bihar - Patel, Deepak Kumar; Kumar, Avinash; Dwivedi, Shripati (Indian Journal of Extension Education, 2023)
This study was conducted in Sattarkataiya block of Saharsa district of Bihar, based on maximum soil health card issued by MBAC, Agwanpur. Two villages named Barahsher and Puroshottampur Purikh were selected based on maximum card holders. Each village selected 100 respondents making a total of 200 Soil Health Card (SHC) holders. A pretested and well structured interview schedule was used to collect data, tabulate, and analyze the results. Farmers faced constraints while adopting a SHC recommendation focused on cereal crops that was identified, documented, and ranked. Major constraints faced by farmers were inadequate follow-up by extension agency (71%); soil sample not taken from each farmer’s field (59%), not getting SHC reports in time (57%) and not using of recommended dose of fertilizers by farmers as per SHC recommendation (49%). While major suggestions that came out to tackle mentioned constraints were that SHC should be issued prior to crop season (70%), Soil sampling laboratory should be established at Block level with highly qualified staff (61%), farmer should be trained to take soil samples (63%). and soil sampling should be based on hands on training of farmer (59%).